Implementation of Bureaucratic Reform to Improve Public Services - Lin, Monica (PT. Riset Press International, 2023)
This study aims to describe the implementation model of bureaucratic reform that has been carried out, both in Indonesia and several other countries. Provide a comprehensive understanding of the importance of bureaucratic reform. The research method used is the library research method from various sources related to bureaucratic reform. The results of this literature review illustrate that the bureaucratic reforms that have been carried out in several countries are generally related to two dimensions, namely the organizational dimension and the dimension of apparatus human resources. In the context of carrying out the implementation of bureaucratic reform at Provincial Bawaslu and Regency/City Bawaslu, what needs to be done immediately is the making and stipulation of a Bureaucratic Reform Team Decision Letter, making and stipulating a Role Model Decree and Bureaucratic Reform Change Agent covering 8 areas of change, preparing an implementation action plan bureaucratic reform, filling out bureaucratic reform evaluation worksheets, monitoring and evaluating the implementation of bureaucratic reform every month.